Syahir, Kamariah named Best Athletes - Nor Salwana, Mohammad Idris (2020)
Kuantan, 28 August 2020 - The staff of the Centre for Sports and Culture, Syahir Ahmad Termizi, 26 was named the recipient of the Sports Award for the Best Male Athlete category at Majlis Apresiasi in conjunction with the Quality & Innovation Day 2020 at the Sports Complex, UMP Gambang Campus recently.